Prevalence of coronary artery disease risk factors in firefighters in the city of Cape Town fire and rescue service - A descriptive study - Jaron Ras; Lloyd Leach (SAGE Publishing, 2021)
Background: Over 45% of firefighter deaths are attributable to sudden cardiac death related to coronary artery disease (CAD), with many of these deaths attributed to comorbidities. The purpose of the study is to determine the prevalence of coronary artery disease (CAD) risk factors in firefighters in the City of Cape Town (CoCT). Design and Methods: The study used a quantitative, cross-sectional and descriptive design. A total of 124 full-time firefighters were conveniently recruited between September and November 2019 from the City of Cape Town Fire and Rescue Service.  Results: The most prevalent CAD risk factors among firefighters were hypertension (33.1%), obesity (37.1%), cigarette smoking (39.5%) and dyslipidaemia (40.3%). A total of 41.9% of firefighters were categorized as low-risk, 54.8% as moderate-risk, and 3.2% as high-risk for CAD. Conclusion: The majority of firefighters had at least one CAD risk factor, with older males having the highest prevalence of multiple CAD risk factors. Compared to other regions of the world, the (CoCT) firefighters have higher prevalence of dyslipidaemia and cigarette smoking. Preventative behavioural strategies and education on CAD should be promoted to mitigate the development of CAD.